Industrial management: implementation of the TPM tool in a coffee industry - Andrade, Polyana Ribeiro de; Patuzzo, Genilson Valotto; Cardoso, Flávia Aparecida Reitz (Brazilian Journal of Production Engineering, 2025)
Conducted in a food industry, the research aimed to train the operational team in the application of Total Productive Maintenance (TPM) to improve maintenance practices. The approach involved data collection and analysis, highlighting challenges such as machine breakdowns and disorganization in the work environment. The implementation of TPM prioritized autonomous maintenance, standardization, and training, resulting in significant improvements. Additionally, the 5S methodology was used to organize the environment, increase efficiency, and standardize tasks. Leadership commitment was a key aspect, and the effectiveness of the process was monitored through the Overall Equipment Effectiveness (OEE) indicator. Autonomous maintenance empowered employees to handle machine breakdowns, failures, and defects, visibly improving operational efficiency. It also contributed to process improvements, including operator training, organization and standardization of the factory layout, as well as the reduction of waste, such as prolonged machine downtime, repetitive equipment failures, and resource inefficiency, resulting in increased productivity and reduced operational costs.